THE SYSTEM OF INDICATORS FOR EVALUATING THE ECONOMIC EFFICIENCY OF AGRICULTURAL PRODUCTION - Kenjaev Toshbolta Aminovich (Journals Park Publishing, 2022)
The article analyzes the system of indicators for evaluating the economic efficiency of agricultural production. In addition, indicators for evaluating the economic efficiency of agricultural production in the regions have been developed.
Keywords: agricultural products, food security, population, forecasting.